Written feedback and continuity of learning in a geographically distributed medical education program. (December 2013) - Harvey, Pam; Radomski, Natalie; O'Connor, Dennis
<x xml:space="preserve">Abstract</x> Background: The provision of effective feedback on clinical performance for medical students is important for their continued learning. Written feedback is an underutilised medium for linking clinical performances over time. Aims: The aim of this study is to investigate how clinical supervisors construct performance orientated written feedback and learning goals for medical students in a geographically distributed medical education (GDME) programme. Methods: This qualitative study uses textual analysis to examine the structure and content of written feedback statements in 1000 mini-CEX records from 33 Australian undergraduate medical students during their 36 week GDME programme. The students were in their second clinical year. Results: Forty percent of mini-CEX records contained written feedback statements. Within these statements, 80% included comments relating to student clinical performance. The way in which written feedback statements were recorded varied in structure and content. Only 16% of the statements contained student learning goals focused on improving a student's clinical performance over time. Very few of the written feedback statements identified forward-focused learning goals. Conclusion: Training clinical supervisors in understanding how their feedback contributes to a student's continuity of learning across their GDME clinical placements will enable more focused learning experiences based on student need. To enhance student learning over time and place, effective written feedback should contain focused, coherent phrases that help reflection on current and future clinical performance. It also needs to provide enough detail for other GDME clinical supervisors to understand current student performance and plan future directions for their teaching.